2011
DOI: 10.1507/endocrj.k10e-224
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between baseline serum 1,5-anhydroglucitol levels and 2-hour post-challenge glucose levels during oral glucose tolerance tests

Abstract: The resulTs of recent studies indicate that postprandial hyperglycemia may be an independent risk factor for the development of macrovascular complications [1,2]. Although tight glycemic control is important to prevent complications of diabetes [3][4][5], many patients who are well controlled based on their HbA1c values have post-challenge hyperglycemia in oral glucose tolerance tests (OGTTs) [6]. 1,5-Anhydroglucitol (1,5-AG), a major 6-carbon dietary monosaccharide, is thought to reflect daily glycemic excurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
(21 reference statements)
4
19
1
Order By: Relevance
“…This suggests that while low concentrations of 1,5-AG are relatively insensitive for the identification of early hyperglycemic states and future diabetes, they may be useful in the setting of overt diabetes. Our findings are consistent with the physiology of 1,5-AG, where plasma concentrations of 1,5-AG are thought to show decreases only at the highest levels of blood glucose and reflect glucose excursions (31-33). …”
Section: Discussionsupporting
confidence: 89%
“…This suggests that while low concentrations of 1,5-AG are relatively insensitive for the identification of early hyperglycemic states and future diabetes, they may be useful in the setting of overt diabetes. Our findings are consistent with the physiology of 1,5-AG, where plasma concentrations of 1,5-AG are thought to show decreases only at the highest levels of blood glucose and reflect glucose excursions (31-33). …”
Section: Discussionsupporting
confidence: 89%
“…However, our derived cut-off value of 11.55 mg/L is similar to that previously reported (10.7 mg/L24; 12 mg/L, 12 14 mg/L2526. The sensitivity of 75.3% and specificity of 71.2% in our measurements with a cut-off value of 11.55 mg/L 1,5-AG concentrations is in a similar range reported (78% and 72%) for predicting blood glucose enhancements of 2-hour post-challenge glucose ≥200 mg/dL in 75 g oral glucose tolerance tests with a 1–5 AG cut-off value of 14.2 μg/mL27. In the present study, we found when comparing the ≤10 mg/L 1,5-AG serum concentration group with the >10 mg/L 1,5-AG serum concentration group, that in the low 1,5 AG diabetics the serum uric acid concentrations were significantly lower, which supports the hypothesis that reabsorption of uric acid in the proximal tubule is inhibited by hyperglycemia1718, because in the low 1,5-AG serum concentration group the HbA1c percentage was significantly higher.…”
Section: Discussionsupporting
confidence: 79%
“…A Japanese population study showed that 14.0 μg/mL was the best value for detecting subjects with diabetes [24]. Similar findings were observed among Japanese male workers (14.2 μg/mL) [26]. In a Chinese study, the mean of 1,5-AG levels was 15.0 μg/mL in subjects with newly diagnosed diabetes and 11.8 μg/mL in subjects with known diabetes [25].…”
Section: Discussionsupporting
confidence: 54%
“…There have been a few studies investigating GA [21-23] and 1,5-AG levels [24-26] to detect subjects with glucose intolerance defined by glucose levels, but no study has examined the diagnostic thresholds of these glycemic measures for diabetes based on the presence of DR, and it is uncertain whether GA and 1,5-AG measurements are applicable as a diagnostic tool for diabetes [27,28]. In addition, in the general Asian community, there are limited data assessing FPG and 2-hour postload glucose (PG) levels associated with the prevalence of DR [14,17,29].…”
Section: Introductionmentioning
confidence: 99%